Evaluación de abonos orgánicos (compost), obtenidos a partir de residuos sólidos orgánicos domiciliarios con plantas indicadoras de lechuga y repollo. proyecto de gestión de residuos sólidos Facultad de Agronomía – San Juan Bautista. 2023 - Huaman Vargas, Liz Stefanny (2024)
The Thesis on the evaluation of compost of household organic solid waste using lettuce and cabbage indicator plants was carried out on the premises of the Horticulture Workshop, located in the Faculty of Agronomy near the town center of Zungarococha, Loreto, whose objectives were aimed at characterizing and analyzing four types of compost of household organic solid waste and their effects on the germination index. root length, hypocotyl length, survival rate, and mortality at 24 and 48 hours. The statistical design used was the Complete Randomized Design (DCA), with 8 treatments (Zungarococha compost plus lettuce; Zungarococha compost plus cabbage; University compost plus lettuce; University compost plus cabbage; Puerto Almendras compost plus lettuce; Puerto Almendras compost plus cabbage; Nina Rumi compost plus lettuce and Nina Rumi compost plus cabbage). The results obtained led to the following conclusions: Factor A1 (Zungarococha Compost was the one with the highest germination rate at both the 48 and 72 hour levels; the effect of Compost had significant effects on the germination of both vegetables evaluated in both lettuce and cabbage; the other variables, specifically on the survival and mortality rates at both 48 and 72 hours, the effects were not significant.